Breastfeeding self-efficacy among adolescent mothers - Renata de Lima Bizerra; Jéssica Pinheiro Carnaúba; Anne Fayma Lopes Chaves; Rebeca Silveira Rocha; Hérica Cristina Alves de Vasconcelos; Mônica Oliveira Batista Oriá (Universidade Federal de Goias, 2015)
The objective of the study was to assess breastfeeding self-efficacy among lactating adolescents. A quantitative study involving 172 lactating adolescents, conducted in 14 Basic Health Units in the northeast cities of Brazil. For data collection, we used a form and the Breastfeeding Self-Efficacy Scale - Short Form. Data were analyzed with a statistical software. Results showed high breastfeeding self-efficacy (84%), with more adherence to the items: "Ensure that my baby is properly latched on for the whole feeding" (91%), and "Always recognize then my baby is finished breastfeeding" (93%), and less referent to feed the baby without using formula (18%) and breastfeed in front of people (14%). We found high breastfeeding self-efficacy in adolescent mothers in our study, showing a new knowledge about this specific public, in general, related to breastfeeding vulnerability.